1993
DOI: 10.1002/ajmg.1320450606
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic biliary atresia and associated anomalies: Etiologic heterogeneity suggested by distinctive patterns of associations

Abstract: Fifty-one cases of extrahepatic biliary atresia (EHBA) with associated anomalies were found in a study of EHBA (251 cases). Analysis of segregation patterns of these anomalies in individual patients suggested the existence of 2 major groups: (1) 15 cases (29.4%) with various combinations of anomalies within the laterality sequence, and (2) 30 cases (58.8%) with one or 2 anomalies mostly involving the cardiac, gastrointestinal, and urinary systems. These latter anomalies did not follow any recognizable pattern.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
68
1
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 61 publications
3
68
1
2
Order By: Relevance
“…Early recognition of liver disease greatly facilitates the care and outcome of infants. A key component of the work-up is measurement of serum conjugated bilirubin levels after 2 weeks which if elevated should prompt the clinician to initiate a workup to determine the cause of neonatal cholestasis 8 . In general, if patient is developing progressive jaundice soon after birth and is still jaundiced at 2 weeks of life, or develops jaundice within 3 months of life, a work up for neonatal cholestasis should begin 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Early recognition of liver disease greatly facilitates the care and outcome of infants. A key component of the work-up is measurement of serum conjugated bilirubin levels after 2 weeks which if elevated should prompt the clinician to initiate a workup to determine the cause of neonatal cholestasis 8 . In general, if patient is developing progressive jaundice soon after birth and is still jaundiced at 2 weeks of life, or develops jaundice within 3 months of life, a work up for neonatal cholestasis should begin 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Although some have been identified in limited number of patients with BA, none are universally isolated or identified in every case (1)(2)(3)(4). In addition, genetic factors have been suggested as the pathogenesis, which is supported by the presence of congenital nonhepatic malformations, including cardiovascular defects, abdominal situs inversus, and sibling occurrence of BA and other congenital biliary disorders (5)(6)(7)(8). From the study of the infectious animal model of BA, there are gaps in our understanding of the immunologic changes that are associated with BA.…”
mentioning
confidence: 99%
“…Several other studies have indicated that there is a subgroup of infants with BA (Ϸ10%-30%) who also have anomalies of situs determination. [8][9][10] This constellation of anomalies may include in a single patient any combination of cardiac situs inversus, bilobed lungs on both sides, abdominal situs inversus, intestinal malrotation, anomalies of portal vein and hepatic artery, polysplenia, or asplenia. It is interesting to note that neither reovirus nor rotavirus was detected in patients with BA and situs anomalies.…”
mentioning
confidence: 99%